Valor nutritivo e condições higiênicas de rapaduras produzidas no Ceará - Oriá, Humberto Ferreira (1990)
Ten samples of "rapadura" from several areas of state of Ceara were studied with regard to Chemical composition, calcium, iron and phosphorous content. The sanitary condition of "rapadura" production was evaluated by microbiological analysis regarding yeast, molds and total and fecal coliforms. The results indicated the presence of carbohydrates in the range of 87 to 90% and the mineral fraction of 1,33 to 1,82%. The sanitary condition vzere considered sactisfactory for all samples analysed.